Optimal medicinal cupping points selection for asthma disease via graph colouring: A preliminary study - Yuhani, Yusof; Mohd Sham, Mohamad; Noraziah, Adzhar; Nurfatihah, Mohamad Hanafi; Elizabeth, Marta; Muhamad Faiz, Abu Bakar; Mohd Adhha, Ibrahim (IOP Publishing, 2019)
Medicinal cupping is a traditional therapy which used by applying a cup on acu-points or cupping points and the pressure inside the cup is reduced so that the skin and superficial muscle layer is drawn into and held in the cup. Since all diseases and pains have their specific area to be cupped, most cupping practitioners usually recognize the cupping points based upon the disease and the patient's complaints. Hence, they will randomly choose the points upon request due to the money constraint. However, there is no mathematical approach on guaranteeing the handy method is optimized. Thus, in this paper, a graph model is proposed on finding the optimal number of cupping points for asthma disease via graph colouring approach. This mathematical model will further benefit to the biomathematics and medical fields, especially to the industrial cupping practitioners.